Validating Online Measures of Cognitive Ability in Genes for Good, a Genetic Study of Health and Behavior. (January 2020) - Liu, MengZhen; Rea-Sandin, Gianna; Foerster, Johanna; Fritsche, Lars; Brieger, Katharine; Clark, Christopher; Li, Kevin; Pandit, Anita; Zajac, Gregory; Abecasis, Gonçalo R.; Vrieze, Scott
Genetic association studies routinely require many thousands of participants to achieve sufficient power, yet accumulation of large well-assessed samples is costly. We describe here an effort to efficiently measure cognitive ability and personality in an online genetic study, Genes for Good. We report on the first 21, 550 participants with relevant phenotypic data, 7, 458 of whom have been genotyped genome-wide. Measures of crystallized and fluid intelligence reflected a two-dimensional latent ability space, with items demonstrating adequate item-level characteristics. The Big Five Inventory questionnaire revealed the expected five-factor model of personality. Cognitive measures predicted educational attainment over and above personality characteristics, as expected. We found that a genome-wide polygenic score of educational attainment predicted educational level, accounting for 4%, 4%, and 2.7% of the variance in educational attainment, verbal reasoning, and spatial reasoning, respectively. In summary, the online cognitive measures in Genes for Good appear to perform adequately and demonstrate expected associations with personality, education, and an education-based polygenic score. Results indicate that online cognitive assessment is one avenue to accumulate large samples of individuals for genetic research of cognitive ability.